Local governments' dependence on tobacco tax revenue: a deterrent to tobacco control in the Republic of Korea - Young Kyung Do; Kidong Park (The World Health Organization, 2009)
OBJECTIVE: To investigate, in the Republic of Korea, whether local governments' participation in an anti-smoking programme supported by the National Health Promotion Fund in 2002-2003 was related to the percentage of local tax revenue comprised by the tobacco consumption tax (TCT). METHODS: Using financial and administrative data on 163 municipalities, the authors estimated logit models of local governments' participation in the anti-smoking programme as a function of the proportion of local tax revenue that came from the TCT and a set of control variables, namely local socioeconomic characteristics and the size of the staff in the local public health centre (PHC). FINDINGS: Local governments that derived a greater percentage of their local tax revenue from the TCT, particularly those that ranked in the upper fourth in terms of this percentage, were less likely to participate in the anti-smoking programme. Insufficient staff in the PHC was also found to be associated with lower participation in the anti-smoking programme. CONCLUSION: Local governments' dependence on revenue from the TCT may be a deterrent to tobacco control in the Republic of Korea.